Welcome to Paradise (shortened version), 1988 (1988)
Video produced for new Cal Poly employee orientation [00:00:07] Picture of palm trees and hawaiian music plays [00:00:28] Narrator says he is about to give a quick sketch of life as a Cal Poly employee and a Central Coast resident [00:01:00] View of coastline and beaches, lakes, old style buildings, wineries, ranches [00:01:30] Aerial shot of San Luis Obispo [00:01:45] Discusses activities downtown [00:02:00] Talks about the Mission downtown (history, events) [00:02:45] View of campus, speaks of events on campus [00:03:05] Shots of various towns surrounding San Luis Obispo [00:03:55] Talks about working for Cal Poly and the CSU system [00:04:30] Views of Cal Poly from the P, talks about size of campus [00:04:52] Tells history of Cal Poly as a school [00:05:05] References motto "Learn by Doing" [00:05:11] Talks about distinguishing factors about Cal Poly [00:05:45] Talks about advantages of working at Cal Poly [00:06:20] Speaks of activities in the University Union and Chumash Auditorium [00:07:15] Narrator talks about Cal Poly events that are open to the public like Poly Royal and football games [00:07:45] Things to do with your Cal Poly ID card [00:08:20] Highlights campus dining and restaurants of campus [00:08:55] Talks about parking on campus and transportation options [00:09:57] Sunset over ocean [00:10:04] Credits